Influencer Credibility as a Digital Advertising Strategy: Its Impact on Social Media Consumers’ Purchase Intentions in Indonesia - Yuvista, Riska; Sagitakasih, Putri (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
In Indonesia’s rapidly evolving digital ecosystem, social media influencers have become central actors in shaping brand–consumer communication and purchasing behavior. This qualitative descriptive study explores how perceptions of influencer credibility influence consumers’ purchase intentions amid increasing media fatigue. Data were collected through semi-structured interviews with 40 purposively selected social media users who actively engage with influencer content on platforms such as Instagram and TikTok. The data were analyzed using Braun and Clarke’s (2006) thematic analysis to identify recurring patterns and meanings. The findings reveal that influencer credibility is primarily constructed through perceived authenticity, honest communication, and congruence between the influencer’s lifestyle and the audience’s values. These elements foster stronger parasocial relationships, enhancing emotional trust and increasing the likelihood of purchase decisions. However, the study also finds that repetitive, overly commercial, or insincere promotional content contributes to media fatigue, which weakens perceived credibility and reduces persuasive effectiveness. Participants emphasized growing skepticism toward influencers who frequently endorse multiple brands without clear relevance or personal experience. Consequently, audiences become more selective and critical in interpreting influencer messages. The study suggests that brands should prioritize value alignment, narrative authenticity, and long-term relationships over follower count or short-term exposure when selecting influencers. By situating influencer credibility and media fatigue within Indonesia’s socio-digital context, this research contributes empirically to influencer marketing literature and provides practical insights for marketers seeking sustainable and trust-based digital advertising strategies.